Lactobacillus plantarum J26 alleviates alcohol-induced oxidative liver injury by regulating the Nrf2 signaling pathway - Hongxuan Li; Shasha Cheng; Yuhong Wang; Yilin Sun; Jiaxin Zhang; Mingshuang Sun; Chaoxin Man; Yu Zhang; Yujun Jiang (Food Science and Human Wellness)
Oxidative stress is one of the main ways to cause alcohol-induced liver injury, and alcoholic liver disease (ALD) has been a common health problem worldwide. Lactic acid bacteria (LAB) is also considered as a potential treatment to alleviate alcohol-induced liver injury. Lactobacillus plantarum J26 is a LAB isolated from Chinese traditional fermented dairy products with excellent probiotic effects. This study aimed to establish a mice model of alcoholic liver injury through acute-on-chronic alcohol feeding and to study the alleviating effect of pre-intake of L. plantarum J26 on alcohol-induced oxidative liver injury and focus on its potential mechanism of alleviating effect. The results showed that pre-intake of L. plantarum J26 could improve liver pathological changes, reduce lipid accumulation, increase mitochondrial ATP and mitochondrial (mtDNA) levels, and alleviate liver injury. In addition, pre-intake L. plantarum J26 can improve the level of short-chain fatty acids (SCFAs) in the intestines in mice, short chain fatty acids can be used as a signaling molecule activation of nuclear factor E2-related factor 2 (Nrf2) signaling pathway to alleviate liver oxidative stress, and maintain mitochondrial homeostasis by regulating the expression of genes related to mitochondrial dynamics and autophagy, thereby reducing cell apoptosis to alleviate alcohol-induced oxidative liver injury.